First report of the mitochondrial DNA sequences of Chukchi Charr (Salvelinus andriashevi, Salmonidae) - Oleinik, Alla G. (Mitochondrial DNA B Resour, 2017)
Three mitochondrial DNA regions were sequenced in two individuals of the Chukchi charr Salvelinus andriashevi from Lake Istihed (Chukotka): the entire gene sequences of cytochrome b and cytochrome c oxidase-1, and control region. The low level of sequence divergence detected between the sequences suggests that S. andriashevi is probably an isolated population of the Taranetz charr S. taranetzi. The genealogy of mtDNA haplotypes confirms the phylogenetic closeness of S. andriashevi, S. taranetzi, Salvelinus sp. 4 (Lake Nachikinskoe), S. krogiusae (Lake Dal’nee), S. boganidae and S. elgyticus (Lake Elgygytgyn), and S. a. erythrinus (NWT).